Misleading manuscripts: Wyclif and the non-wycliffite bible - Wilks, Michael ca. 20. Jh. (Studies in church history, 1975)
The precise nature of Wyclif’s connection with the production of the first English bible is shrouded in mystery, a subject for the fierce controversy and debate that is possible only where ignorance and uncertainty prevail. To begin with, there is an almost total absence of reliable contemporary evidence. The first statements explicitly attributing authorship to Wyclif do not occur until the generation after his death. Of these, the earliest is that of the chronicler Henry Knighton, whose contacts with early lollardy might make him appear to be a more reliable source than most. Writing perhaps in the mid-1390s, Knighton referred back to the year 1382 as the time when Wyclif translated the gospel, which Christ had given to the clergy and doctors of the church, into the tongue, not of the angels, but of the Angles.